SOA-based multi-wavelength laser using fiber Bragg gratings - Ahmad, Harith; Sulaiman, Abdul Hadi; Shahi, Sharifeh; Harun, Sulaiman Wadi (IOP Publishing, 2009)
We propose and experimentally demonstrate a triple-wavelength fiber ring laser using a semiconductor optical amplifier (SOA) in conjunction with a series of fiber Bragg gratings (FBGs). The three channels operate at 1554.4, 1555.3, and 1556.1 nm with a peak power above -25 dBm and optical signal-to-noise (OSNR) above 30 dB at SOA drive current of 350 mA under the room temperature. The proposed laser configuration has the advantages of a simple and compact structure, multi-wavelength operation and the system can be upgraded to generate more wavelengths by increasing the number of FBG used.